THE EFFECT OF INQUIRY-BASED LEARNING ON READING PERCEPTION TO ELEMENTARY STUDENTS - Seam, Chanthoul (Asosiasi Dosen Perguruan Tinggi Islam, 2025)
This study investigates the effect of Inquiry-Based Learning (IBL) on elementary students' reading perception at a private school in Cambodia. IBL is a student-centered instructional strategy that fosters active participation, curiosity, and critical thinking through exploration and discovery. This research employed a mixed-methods approach, combining quantitative data from a questionnaire distributed to 50 students (selected from a population of 150) and qualitative data to provide deeper insights into students' attitudes and engagement with reading activities. Descriptive statistics were analyzed using SPSS 20.0. The findings reveal that the use of IBL positively impacts students' reading perception by enhancing motivation, comprehension, and active involvement in learning tasks. Students reported greater interest in reading when lessons were inquiry-driven, interactive, and connected to real-world contexts. Additionally, the study underscores the important role of teachers and school leaders in implementing effective IBL strategies. By promoting student autonomy and a sense of ownership in the learning process, IBL can improve literacy outcomes and foster lifelong reading habits. These results suggest that incorporating IBL into primary education, especially in language instruction, can significantly enrich the learning experience and contribute to more meaningful and student-centered education.